International Student Collaboration in Efforts to Raise Public Awareness of COVID-19 Prevention - Ismail, Faisal Husen; Rohmah, Rohmah; Ibrahim, Intan Nur Syaheera; Wen, Cheam Kai (ASEAN Journal of Community Engagement, 2021)
This study evaluates the enforcement of public health protocols in deciding the COVID-19 distribution chain. The evaluation is based on contributions among international students in higher education and examined their experiences and activities engaging in activities against the COVID-19 epidemic. The research focuses on the collaborative activities of students of Universiti Tun Hussein Onn Malaysia with Sultan Maulana Hasanuddin State Islamic University Banten, Indonesia. Through observation and direct and online involvement with the community, the study is qualitative and employs an inductive approach. Survey feedback was received in collaboration with five students from each university. This study is qualitative using an inductive approach, through observation and direct interaction with the community. The results show that there are still among the public in Santri Village who ignore the dangerous threat of COVID-19 to their health. The results also found that the community did not fully implement the health protocol. This study proposes a more detailed study of the attitudes of communities ignoring the dangerous threat of disease outbreaks to themselves. This collaboration faces constraints from the point of view of not yet yielding optimal results and requiring more creative efforts to help the community increase their awareness to carry out health protocols in times of disaster.